Microstructure, high-temperature mechanical and dielectric properties of novel Si3N4 f/SiNO wave-transparent composites. Issue 10 (August 2022) - Cao, Shuwei; Zhang, Dahai; Wang, Jinming; Zhang, Jingyi; Zhang, Juan; Yao, Rui; Yao, Yao; Zhang, Yue
Abstract: Continuous Si3 N4 fiber reinforced SiNO matrix composites (Si3 N4 f /SiNO composites) were innovatively prepared for long-time high-temperature resistant wave-transparent materials of hypersonic aircraft. The microstructure, high-temperature mechanical and dielectric properties of Si3 N4 f /SiNO composites were investigated in detail. The as-fabricated Si3 N4 f /SiNO composites have homogeneous SiNO matrix distribution for the special winding process, which is beneficial for the mechanical strength and wave-transparent properties. The average tensile strength and flexural strength at room temperature is 87.8 MPa and 171.2 MPa respectively, which suggests Si3 N4 f /SiNO composites have excellent mechanical strength. The tensile strength value decreases to 54.6 MPa after heat-treated at 1000 ℃ for the surface reactions between the SiNO matrix and Si3 N4 fibers. After heat-treated at 1550 ℃, the composites have the tensile strength value of 24.2 MPa for the high strength retention rate of Si3 N4 fibers at this temperature. Si3 N4 f /SiNO composites have excellent room temperature dielectric properties and excellent dielectric stability in different frequency bands (7–18 GHz). The dielectric constant values vary from 3.69 to 3.75 while the dielectric loss attains the order of 10 −3 . The dielectric constants and dielectric loss of Si3 N4 f /SiNO composites are relatively stable from RT to 800 ℃. The as-fabricated Si3 N4 f /SiNO composites that have excellent high temperature resistance and dielectric properties are the ideal high temperature wave-transparent composites.